Identification of Genes in Xanthomonas euvesicatoria pv. rosa That Are Host Limiting in Tomato - Qiurong Fan; Shaheen Bibi; Gary E. Vallad; Erica M. Goss; Jason C. Hurlbert; Matthews L. Paret; Jeffrey B. Jones; Sujan Timilsina (Plants, 2022)
Xanthomonas euvesicatoria pv. rosa strain Xer07 causes a leaf spot on a Rosa sp. and is closely related to X. euvesicatoria pv. euvesicatoria (Xee) and X. perforans (Xp), causal agents of bacterial spot of tomato. However, Xer07 is not pathogenic on tomato and elicits a hypersensitive reaction (HR). We compared the genomes of the three bacterial species to identify the factors that limit Xer07 on tomato. Comparison of pathogenicity associated factors including the type III secretion systems identified two genes, xopA and xer3856, in Xer07 that have lower sequence homology in tomato pathogens. xer3856 is a homolog of genes in X. citri (xac3856) and X. fuscans pv. aurantifolii, both of which have been reported to elicit HRs in tomato. When xer3856 was expressed in X. perforans and infiltrated in tomato leaflets, the transconjugant elicited an HR and significantly reduced bacterial populations compared to the wildtype X. perforans strain. When xer3856 was mutated in Xer07, the mutant strain still triggered an HR in tomato leaflets. The second gene identified codes for type III secreted effector XopA, which contains a harpin domain that is distinct from the xopA homologs in Xee and Xp. The Xer07-xopA, when expressed in X. perforans, did not elicit an HR in tomato leaflets, but significantly reduced bacterial populations. This indicates that xopA and xer3856 genes in combination with an additional factor(s) limit Xer07 in tomato.